Real and counterfeit cores: how feedback expands halos and disrupts tracers of inner gravitational potential in dwarf galaxies - Jahn, Ethan D; Sales, Laura V; Marinacci, Federico; Vogelsberger, Mark; Torrey, Paul; Jia Qi; Smith, Aaron; Li, Hui; Kannan, Rahul; Burger, Jan D; Zavala, Jesús (arXiv.org, 2021)
The tension between the diverging density profiles in Lambda Cold Dark Matter (\(Λ\)CDM) simulations and the constant-density inner regions of observed galaxies is a long-standing challenge known as the `core-cusp' problem. We demonstrate that the SMUGGLE galaxy formation model implemented in the Arepo moving mesh code forms constant-density cores in idealized dwarf galaxies of \(M_\star ≈ 8 × 10^7\) M\(_{\odot}\) with initially cuspy dark matter halos of \(M_{200} ≈ 10^{10}\) M\(_{\odot}\). Identical initial conditions run with the Springel and Hernquist (2003; SH03) feedback model preserve cuspiness. Literature on the subject has pointed to the low density threshold for star formation, \(ρ_\text{th}\), in SH03-like models as an obstacle to baryon-induced core formation. Using a SMUGGLE run with equal \(ρ_\text{th}\) to SH03, we demonstrate that core formation can proceed at low density thresholds, indicating that \(ρ_\text{th}\) is insufficient on its own to determine whether a galaxy develops a core. We suggest that the ability to resolve a multiphase interstellar medium at sufficiently high densities is a more reliable indicator of core formation than any individual model parameter. In SMUGGLE, core formation is accompanied by large degrees of non-circular motion, with gas rotational velocity profiles that consistently fall below the circular velocity \(v_\text{circ} = \sqrt{GM/R}\) out to \(\sim 2\) kpc. This may artificially mimic larger core sizes when derived from observable quantities compared to the size measured from the dark matter distribution (\(\sim 0.5\) kpc), highlighting the need for careful modeling in the inner regions of dwarfs to infer the true distribution of dark matter.